A Survey of Preoperative, Perioperative, and Postoperative Management Practices for Testicular Torsion in Pediatric Patients among European Surgeons - Beher, Amit; Moreno-Alfonso, Julio César; Garnier, Hanna; Darici, Dogus; Salö, Martin Jonathan; Aubert, Ophelia (European Journal of Pediatric Surgery, 2024)
Introduction Management of testicular torsion varies between specialties resulting in lack of standardization. The aim of this survey was to assess pre-, peri-, and postoperative differences.Methods An online questionnaire was distributed in 2023 to general and pediatric surgeons, pediatric urologists, and urologists by the Trainees of European Pediatric Surgery.Main Results Among 88 respondents (92% tertiary referral hospital), 38% always or usually perform sonography in case of suspected torsion respectively. In addition, 15% always attempt manual detorsion and 44% depending on the clinical presentation. Most surgeons (93%) favor a scrotal approach. Interestingly, pediatric surgeons choose a transscrotal while other specialties opt for a midline incision (p = 0.002). The majority (57%) employ a three-point fixation, while 42% opt for a two-point fixation. In case of necrotic testis, 61% puncture the testis with 52% opting for surgical removal, while 33% perform orchiectomy and 6% leave it in situ. Regarding necrotic or borderline-appearing testis, 54% take a biopsy. Furthermore, 82% perform prophylactic orchidopexy of the contralateral side during the same session. Postoperative antibiotics are always administered by 12%, while 52% do so sometimes. Most perform sonographic (58%) or clinical (57%) follow-up 3 months postoperatively. Notably, pediatric surgeons and urologists perform follow-up more frequently themselves, while general surgeons/urologists recommend follow-up by pediatricians (p = 0.002). In addition, 76% of responders affirm adhering to European Association of Urology guidelines. Unawareness of guidelines and institutional practices are reasons most commonly cited for nonadherence.Conclusion Our study reveals significant disparities in the pre-, peri-, and postoperative management of testicular torsion underscoring the need for establishing standardized practices.
Keywords: testicular torsion; children; clinical practice; guidelines; surgery